The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1258/002367789780810590
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide as a short-term restraint anaesthetic in rats with subclinical respiratory disease

Abstract: SummaryThe use of carbon dioxide (C0 2 ) with, and without, oxygen (0 2 ) as a short-term restraint anaesthetic for Wistar rats in which subclinical respiratory disease was endemic, was assessed in 3 separate experiments. In the first, rats were placed in a CO 2 atmosphere generated from solid CO 2 chips in a 70 Iplastic bin, and removed at time intervals ranging from 0 to 120 s after disappearance of the pedal reflex. Eight of 25 rats died, including 2 which were removed immediately the pedal reflex disappear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…1986, Blackshaw et a1. 1988, Fenwick & Blackshaw 1989, Urbanski & Kelly 1991, Dannemann et a1. 1994, Fodor 1995.…”
unclassified
“…1986, Blackshaw et a1. 1988, Fenwick & Blackshaw 1989, Urbanski & Kelly 1991, Dannemann et a1. 1994, Fodor 1995.…”
unclassified
“…There are contra- dictory reports on pain or distress in animals being anaesthetised or euthanised with CO 2 (Mikeska and Klemm 1975;Feldman and Gupta 1976;Fenwick and Blackshaw 1989;Urbanski and Kelley 1991;Hewett et al 1993;Berger-Sweeney et al 1994;Coenen et al 1995;Danneman et al 1997). Danneman et al (1997) have reported that the concentrations that are least likely to cause pain and distress are associated with histological changes in the lungs.…”
Section: Resultsmentioning
confidence: 99%
“…This CO 2 mixture is volatile, non-£ammable, odourless, and colourless. Fenwick and Blackshaw (1989) described a method for short-term anaesthesia in rats with subclinical respiratory disease using CO 2 /O 2 (80:20). Lukas (1994) reported the use of a 60:40 mixture to produce light anaesthesia for blood sampling in rodents.…”
Section: Anaesthesia Techniquesmentioning
confidence: 99%
“…Concerning carbon dioxide / oxygen mixtures, a different opinion can be found in a paper by Hoenderken et al (1994). The authors refer to AVMA (1986), van den Bogaard, Dam andWeekers (1985), van Luytelaar et al (1993), and Fenwick and Blackshaw (1989), who claim that adding oxygen to carbon dioxide , in contrast to using carbon dioxide in air, reduces signs of asphyxia and excitation in rats and can therefore be beneficial for anaesthetising rats (see papers by Leach et al that showed that in choice tests, rats found levels of carbon dioxide more than 20% aversive). In the other series of experiments with chickens, the conclusion drawn was that adding oxygen to carbon dioxide atmospheres and moistening the very dry technical gases are beneficial for animal welfare.…”
Section: Gas Stunningmentioning
confidence: 99%